The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1002/jssc.201500013
|View full text |Cite
|
Sign up to set email alerts
|

Microextraction methods for the determination of phthalate esters in liquid samples: A review

Abstract: 1,2-Benzenedicarboxylic acid esters, commonly referred to as phthalate esters, form a group of compounds that are mainly used as plasticizers in polymers. Because phthalate esters are not chemically bound to the plastics, they can be released easily from products and migrate into the food or water that comes into direct contact. Due to their widespread use, they are considered as ubiquitous environmental pollutants. Phthalate esters are regarded as endocrine disrupting compounds by means of their carcinogenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 48 publications
(16 citation statements)
references
References 93 publications
2
14
0
Order By: Relevance
“…The findings are in line with earlier literature [69][70][71] which found that adsorption onto materials of natural origin is characterized by complex mechanisms, related to the heterogeneous surface of natural adsorbents and presence of a diversity of functional groups on the surface of a biomass. Therefore, several physical and chemical interactions may occur together during the sorption process.…”
Section: Proposed Adsorption Mechanismsupporting
confidence: 92%
See 1 more Smart Citation
“…The findings are in line with earlier literature [69][70][71] which found that adsorption onto materials of natural origin is characterized by complex mechanisms, related to the heterogeneous surface of natural adsorbents and presence of a diversity of functional groups on the surface of a biomass. Therefore, several physical and chemical interactions may occur together during the sorption process.…”
Section: Proposed Adsorption Mechanismsupporting
confidence: 92%
“…Calculations were made of the free energy (ΔG ), enthalpy (ΔH ) and entropy (ΔS ) of the systems, using Eqs. (8)(9)(10): Chitosan cross-linked with glutaraldehyde 113.00 Pb 2þ [54] GLA-cross-linked metal-complexed chitosan 105.26 Pb 2þ [55] Chitosan/cotton fibers 101.53 Pb 2þ [56] Wheat bran 79.40 Pb 2þ [57] Chitosan/clay beads 72.31 Cd 2þ [58] Chitosan-alginate beads 60.27 Pb 2þ [59] Fly ash porous pellet 45.54 Pb 2þ [60] Wheat straw 41.84 Ni 2þ [61] Seed husk of Calophyllum inophyllum 34.51 Pb 2þ [62] Chitosan/glutaraldehyde 32.90 Cd 2þ [63] Hazelnut shell 28.18 Pb 2þ [64] Hyacinth roots 24.94 Pb 2þ [65] De-oiled allspice husk 20.79 Pb 2þ [66] Coal fly ash 18.98 Cd 2þ [67] Tea factory waste 18.42 Ni 2þ [68] Al-impregnated fly ash 15.75 Ni 2þ [69] Chitosan/cotton fibers (via Schiff base bond) 15.74 Cd 2þ [56] Wheat bran 12.00 Ni 2þ [70] Chitosan/cotton fibers (via Schiff base bond) 7.63 Ni 2þ [56] Results of the present study are marked in bold. where ΔG o (kJ/mol) is the change in the free energy of the system, ΔH o (kJ/mol) is the change in the free enthalpy of the system, ΔS o (kJ mol À1 K À1 ) is the change in the free entropy of the system, R (8.314 J mol À1 K À1 ) is the gas constant, K c is the reaction equilibrium constant, and T (K) is the temperature.The changes in enthalpy and entropy were calculated based on the plot of lnK c vs. 1/T, using its slope (À ΔH o R ) and y-axis intercept…”
Section: Thermodynamic Studiesmentioning
confidence: 99%
“…As reported in Table , the extraction efficiency ranged between 10–12 and 2–3% for HMHA and 3MSH, respectively, depending on the concentration level. The extraction efficiency values obtained are comparable to similar methods that use DI‐SPME extraction for the determination of other compounds, such as polycyclic aromatic hydrocarbons , phthalate esters , and pesticides . It must be noted that, in several studies , the extraction efficiency was considerably improved when using HS‐SPME extraction instead of DI‐SPME, especially when analyzing non‐polar compounds.…”
Section: Resultssupporting
confidence: 58%
“…Moreover, SPME generally provides low detection limits and good reproducibility both in headspace and in direct immersion (DI) mode [23][24][25][26]. In DI mode, SPME was successfully tested in aqueous systems for the determination of organic compounds [27][28][29][30][31], proving a promising alternative to conventional extraction methods.…”
Section: Introductionmentioning
confidence: 99%
“…Extraction techniques which frequently are used include liquid extraction method such as LLE LPME , dispersive liquid–liquid microextraction , SPE , SPME , and stir bar sorptive extraction . In the past decades, SPE as a popular sample preparation technique in environmental, food, and biomedical analyses has been applied .…”
Section: Introductionmentioning
confidence: 99%